Encounters involving planetary systems in birth environments: the significant role of binaries. Issue 1 (25th September 2020) - Li, Daohai; Mustill, Alexander J; Davies, Melvyn B
ABSTRACT: Most stars form in a clustered environment. Both single and binary stars will sometimes encounter planetary systems in such crowded environments. Encounter rates for binaries may be larger than for single stars, even for binary fractions as low as 10–20 per cent. In this work, we investigate scatterings between a Sun–Jupiter pair and both binary and single stars as in young clusters. We first perform a set of simulations of encounters involving wide ranges of binaries and single stars, finding that wider binaries have larger cross-sections for the planet's ejection. Secondly, we consider such scatterings in a realistic population, drawing parameters for the binaries and single stars from the observed population. The scattering outcomes are diverse, including ejection, capture/exchange, and collision. The binaries are more effective than single stars by a factor of several or more in causing the planet's ejection and collision. Hence, in a cluster, as long as the binary fraction is larger than about 10 per cent, the binaries will dominate the scatterings in terms of these two outcomes. For an open cluster of a stellar density 50 pc −3, a lifetime 100 Myr, and a binary fraction 0.5, we estimate that Jupiters of the order of 1 per cent are ejected, 0.1 per cent collide with a star, 0.1 per cent change ownership, and 10 per cent of the Sun–Jupiter pairs acquire a stellar companion during scatterings. These companions are typically thousands of au distant and in half of the cases (so 5 per cent of all Sun–Jupiter pairs), they can excite the planet's orbit through Kozai–Lidov mechanism before being stripped by later encounters. Our result suggests that the Solar system may have once had a companion in its birth cluster.